Doing Well by Blowing Right: How Whistleblowing Practice Enhances Corporate Risk Disclosure - Dewi Mustika Ratu (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
Given the prevalence of corruption scandals in State-Owned Enterprises (SOEs), it is crucial to assess the effectiveness of whistleblowing systems in promoting transparency of risk management information. Therefore, this study investigates the relationship between whistleblowing practices and the level of corporate risk disclosure. Using archival methods, observations were conducted between 2016 and 2021 at SOEs listed on the Indonesia Stock Exchange (IDX). As expected, using stakeholder theory and the